2011
DOI: 10.1590/s0006-87052011000400019
|View full text |Cite
|
Sign up to set email alerts
|

Use of local rice cultivars as additional differentials to identify pathotypes of Pyricularia oryzae

Abstract: Eight additional rice cultivars as differentials were selected to identify pathotypes occurring in the Tocantins State. They were BRS Jaburu, BRS Taim, BRS Biguá, BR IRGA-417, Epagri 109, Javaé, Metica-1 and Supremo. These differentials were used in addition to the international set to determine the pathogenic diversity of 193 Pyricularia oryzae isolates collected during 1994-2002 from irrigated rice cultivars. They were conserved in Pyricularia culture collection of Embrapa Rice and Bean Research center. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Previous studies also indicated that the high diversity of pathogenicity or molecular lineage of M. oryzae could be induced by different rice cultivars. [5][6][7]12) Our results demonstrated that the isolates of M. oryzae from Chiayi were diversely associated with a number of rice cultivars, and the predominant groups were distributed over the rice production area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also indicated that the high diversity of pathogenicity or molecular lineage of M. oryzae could be induced by different rice cultivars. [5][6][7]12) Our results demonstrated that the isolates of M. oryzae from Chiayi were diversely associated with a number of rice cultivars, and the predominant groups were distributed over the rice production area.…”
Section: Discussionmentioning
confidence: 99%
“…3,4) Recent studies also showed that pathogenicity of P. oryzae to different rice cultivars or lines differs in different countries, including Argentina, 5) Brazil, [6][7][8] China, 9) USA, 10) Thailand, 11) and Vietnam. 12) In Taiwan, more than 78 races of P. oryzae had been identified using 8 standard lines of rice as differentials.…”
Section: Introductionmentioning
confidence: 99%